Factor-XII Congenital Deficiency. A New Family Study - Lucia, J F; Ercoreca, L; Torres, M; Giralt, M; Raichs, A (Thrombosis and Haemostasis, 1979)
This report describes two people in a family with Hageman trait (homozygotes) (Factor XII = 0.06%). In addition eight family members were studied to evaluate the inheritance of this congenital deficiency. A study of the Kallikrein-Kininogen system induced by the fragments of Factor XII was also carried out.It is concluded that the inheritance is as described by Veltkamp and that the Kallikrein release from the prekallikreinogen (Fletcher factor) “in vitro” is related to the amount of Factor XII procoagulant protein.